2008
DOI: 10.1094/php-2008-0519-01-rs
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Sorghum Germplasm from China against Claviceps africana, Causal Agent of Sorghum Ergot

Abstract: Forty Chinese sorghum landraces maintained by the USDA-ARS Plant Genetic Resources Conservation Unit, Griffin, GA were evaluated for ergot resistance at the Texas A&M Research Farm, College Station, Texas, during the 2005 and 2006 growing seasons. The male sterile line, ATx623, was included as a susceptible control and three IS8525 derived lines were included as resistant controls. The disease infection level was low in the susceptible check in 2005 due to unfavorable environmental conditions, but the majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…In Zimbabwe and India, a yield loss of 20-80% had been reported in hybrid seed production due to ergot [13,14]. A report from southern Africa, Mexico, and the United States indicated that a yield loss of up to 80% and 50% was observed in hybrid sorghum seed and grain production, respectively [15,16]. Honeydew-contaminated grain has reduced feed intake and causes toxicity when fed to livestock [17].…”
Section: Introductionmentioning
confidence: 99%
“…In Zimbabwe and India, a yield loss of 20-80% had been reported in hybrid seed production due to ergot [13,14]. A report from southern Africa, Mexico, and the United States indicated that a yield loss of up to 80% and 50% was observed in hybrid sorghum seed and grain production, respectively [15,16]. Honeydew-contaminated grain has reduced feed intake and causes toxicity when fed to livestock [17].…”
Section: Introductionmentioning
confidence: 99%